The shifting of traditional understanding of citizenship due to international migration - Paparusso, Angela; Wihtol de Wenden, Catherine (Frontiers in Sociology, 2025)
This article analyzes how migration has profoundly influenced the conception of citizenship by challenging the traditional state-citizen relationship and introducing transnational and European citizenship, which disconnects nationality from civic rights. In particular, our research questions are how migration has reshaped the conception of citizenship and what challenges migrants, refugees, stateless individuals, asylum seekers and environmentally displaced persons face in obtaining legal status in host countries. France is presented as a case study of the negotiations shaping the evolution of the conception of citizenship in relation to migration. Our literature review-based research highlighted the dissociation between nationality and citizenship and the emergence of migrant practices, like dual citizenship, transnationalism, and naturalization, which have redefined borders and forms of belonging, focused on residency and participation. Countries with long immigration histories have embraced diversity, multiculturalism, and anti-discrimination policies to integrate migrants. However, most people from the Global South face barriers to legal migration, resulting in populations without formal status, amid rising resistance to greater inclusion led by populist forces.